Synergistic therapy of Chinese herbal medicine and gut microbiota modulation for post-stroke cognitive recovery: focus on microbial metabolite and immunoinflammation - Ge, Shihui; Zhang, Shuangli; She, Linjing; Gu, Tianning; Wang, Shicong; Huang, Xin; Wang, Lanlan; Miao, Mingsan (Frontiers in Microbiology, 2025)
Post-stroke cognitive impairment (PSCI), a common complication following stroke, significantly impacts patients' quality of life and rehabilitation. Recent studies have highlighted the role of gut microbiota and their metabolites in modulating immunoinflammation and cognitive function via the gut-brain axis. Traditional Chinese medicine (TCM) and microbiota interventions including probiotics and fecal microbiota transplantation, have shown potential in reshaping gut microbial communities and metabolite profiles. Some studies suggest that combining these approaches via identical or related therapeutic mechanisms may yield enhanced efficacy in treating Post-Stroke Cognitive Impairment (PSCI). These findings establish a theoretical foundation for future research and clinical practice. This review systematically examines the mechanistic role of gut microbial metabolites in neuroimmune modulation and comprehensively evaluates the therapeutic potential of combined TCM and microbiota-targeted therapies for PSCI, adopting a multifactorial approach that addresses neuroinflammation, microbial dysbiosis, and metabolic dysregulation.